Treating Tumors at Low Drug Doses Using an Aptamer–Peptide Synergistic Drug Conjugate. (21st December 2018) - Pusuluri, Anusha; Krishnan, Vinu; Lensch, Valerie; Sarode, Apoorva; Bunyan, Elaine; Vogus, Douglas R.; Menegatti, Stefano; Soh, H. Tom; Mitragotri, Samir
Abstract: Combination chemotherapy must strike a difficult balance between safety and efficacy. Current regimens suffer from poor therapeutic impact because drugs are given at their maximum tolerated dose (MTD), which compounds the toxicity risk and exposes tumors to non‐optimal drug ratios. A modular framework has been developed that selectively delivers drug combinations at synergistic ratios via tumor‐targeting aptamers for effective low‐dose treatment. A nucleolin‐recognizing aptamer was coupled to peptide scaffolds laden with precise ratios of doxorubicin (DOX) and camptothecin (CPT). This construct had an extremely low IC50 (31.9 nm ) against MDA‐MB‐231 breast cancer cells in vitro, and exhibited in vivo efficacy at micro‐dose injections (500 and 350 μg kg −1  dose −1 of DOX and CPT, respectively) that are 20–30‐fold lower than their previously‐reported MTDs. This approach represents a generalizable strategy for the safe and consistent delivery of combination drugs in oncology.